Specificities of the formation of epoxy-acrylate interpenetrating polymer networks under the Sun radiation - Samoilenko, T. F.; Iarova, N.V.; Menzheres, G.Y.; Brovko, O. O. (Reports of the National Academy of Sciences of Ukraine, 2014)
Kinetic specificities of the simultaneous epoxy-acrylate interpenetrating polymer networks synthesis under the solar radiation are investigated. The comparative analysis of the degree of functional groups conversion for the polymerization under artificial and natural conditions is made. It is found that the epoxy groups conversion is higher under the solar irradiation than under the irradiation of a UV lamp, and the double bonds conversion is actually the same for both systems.